Pengembangan Bahan Ajar Flipbook Berbasis Problem Based Learning untuk Meningkatkan Pemahaman IPAS pada Siswa Kelas V Sekolah Dasar - Garsela Syakila Widyatama; Desi Wulandari (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to research and develop (R&D) flipbook teaching materials based on the problem-based learning model for Class V Light materials. The development model used is Borg and Gall. Data were obtained by test and non-test methods. The test method is derived from the results of the pretest and posttest, while the non-test method is derived from the results of questionnaires, data, observations, interviews, and documents. The subject of the trial is a student of class V. In this research, media validators gave an average percentage of 90% product validation assessments, while material validators gave an average percentage of 93.33%. Both categories are considered very feasible. Both the pretest and posttest results for the student indicate progress. This is demonstrated by the 42.43 average difference between the pretest and posttest as well as a high N-Gain of 0.8106.  Since the obtained N-Gain is greater than 0.70, it is regarded as high. From the improvement in student learning outcomes, it can be concluded that the use of flipbook teaching materials in class V light materials can improve student understanding.